Effect of energy input on wear behaviour of SiC surface modified layer duplex stainless steel - Paijan, Lailatul Harina; Maleque, Md. Abdul (2017)
Duplex stainless steel (DSS) contains equilibrium amount of ferrite and austenite phase exhibits tremendeous corrosion resistance and mechanical properties. However, DSS having drawbacks on low surface hardness and wear resistance in the various industries in oil and gas for piping, drilling rigs and boiler, chemical and cargo tanks and heavy construction vehicle for hydraulic pump piston and transmission gear for bulldozer and excavator. Improvements in these limitations significantly increase the usage in wider applications. Maleque et al. [1] investigated the TiC composite coating on AISI 4340 using TIG torch method. Both microhardness and wear resistance showed significant improvement particularly after TIG coating with AISI 4340. Other finding by Adeleke et al. [2] studied the Fe-C-Si coatings on CP-Ti melted under TIG torch techniques. The hardness value increased of 800 Hv compared to 200 Hv of substrate material. The wear behavior also improved with lower wear rate and coefficient of friction compared to substrate material. Yet, no study has been carried out to melt the SiC powder with DSS by using TIG techniques for surface modification. Therefore, the purpose of this work to investigate the wear behavior of DSS surface with SiC powder preplacement melted at energy input of 480, 768 and 1728 J/mm. The microhardness and wear behavior are presented in this paper.